Increased Awareness of Clean and Healthy Living Behavior in Elementary School Children through the PHBS Socialization Program (CTPS and Oral Health) - Nasution, Lisda Rimayani; Irvan H Noho; Anggri Ani Hidayat; Syarifah Elly; Damanik, Fadilla Munawaroh; Br Karo Ujung, Revina Natalya; Dina Salia; Sitepu, Zefanya Nesha Endhaiya (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Human development is being promoted on an scale by the Indonesian government. The human development index (ipm) of 2021 reached 72.29 percent, showing an increase of 0.35 percent. Ipm improvements can be made through various sectors, health among them. Yet, hand washing and dental and oral health are among the problems faced by school-age children. The method of carrying out the activity is to use the method of speaking and demonstration with the participants of 30 third-grade students in the country of 024772 east binjai. The activity resulted in increased knowledge and awareness of state elementary school students 024772 east binjai demonstrated with the student's willingness and ability to practice good and proper hand washing and brushing of teeth.